Comparison of Archaeal Populations in Soil and Their Encapsulated Iron-Manganese Nodules in Four Locations Spanning from North to South China. Issue 9 (21st October 2017) - Zhang, Gui-You; Zhang, Li-Mei; He, Ji-Zheng; Liu, Fan
ABSTRACT: To characterize the archaeal community composition in soil originating iron-manganese nodules, four types of soils—brown soil, yellow-cinnamon soil, yellow brown soil and red soil—and their associated iron-manganese nodules were collected from Queyu (QY), Zaoyang (ZY), Wuhan (WH) and Guiyang (GY), China, respectively, and subjected to quantitative polymerase chain reaction, cloning and sequencing analyses. The results showed that the archaeal 16S rRNA gene copy numbers in nodules, ranging between 3.59 × 10 2 and 4.17 × 10 3 copies g −1 dry nodule, were about 50–1000 times lower than those in their corresponding soils (1.87 × 10 5 to 1.08 × 10 6 copies g −1 dry soil), correlating with the low organic matter in the nodules, while archaea accounted for a relatively higher proportion of total prokaryote in nodules than in soils. Community composition analysis suggested that the archaeal diversity in both soils and nodules were much lower than bacterial, but archaeal community structures were similar to each other among the soils and nodules from the same location but varied among four locations, converse to the previous observation that bacterial community shifted markedly between nodules and soils as the result of habitat filtering. The archaeal communities in both soils and nodules were predominated by Thaumarchaeota Group I.1b with the relative abundance ranging between 73.88 and 94.17%, except that Euryarchaeota dominated the archaeal community in one nodule sample (WHn) developed from lake sediment. The finding shed new light on the archaeal diversity and their ecophysiology in different habitats, and further supported the opinion that archaea are more adaptable to stress and unfavorable conditions.